Implementasi Program Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Di RSUD Nene Mallomo Kabupaten Sidrap - Chairunnisa; Reza Aril Ahri; Nurul Hikmah B (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
The number of data from the South Sulawesi Provincial Health Office and National Health Insurance (JKN) participants in Sidenreng Rappang Regency is 228,687 people. This consists of 180,654 people as Contribution Assistance Recipients (PBI) and 48,033 as Non-Contribution Assistance Recipients (Non-PBI). This study uses a qualitative research type with a descriptive approach that aims to determine how the Implementation of the Social Security Administering Agency (BPJS) Health program at Nene Mallomo Hospital, Sidrap Regency, by going directly to the field to obtain information and conduct observations. The informants for this study were the Hospital Director, Hospital Staff, and BPJS Health Participants at Nene Mallomo Hospital, Sidrap Regency. Data was collected through interviews, observations, and documents related to the problem being studied. From the study results, it was obtained that the queue time when queuing was quite long, especially in the morning during peak hours. In addition, Nene Mallomo Hospital also receives monthly evaluations from BPJS Kesehatan regarding many things that are input; from the review, Nene Mallomo Hospital received input related to not implementing existing regulations, such as lack of drugs in the hospital pharmacy and patients having to buy drugs outside. It is hoped that the hospital will improve its human resources to help speed up the service process so that queues can be reduced and conduct socialization related to the BPJS Kesehatan program because there are still many BPJS participants who do not know their rights and obligations.